2008
DOI: 10.1002/clc.20355
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Emerging Cardiovascular Risk Factors in Younger Individuals with a Family History of Premature Coronary Heart Disease and Low Framingham Risk Score

Abstract: Introduction: The purpose of this study was to assess the prevalence of emerging cardiac risk factors in individuals with a family history of premature coronary heart disease (CHD) and who were predicted to be low-risk for cardiovascular (CV) disease based on their Framingham risk score. Methods: We prospectively evaluated 89 younger men and women with a family history of premature CHD and who had a low Framingham risk score. Patients with CHD or CHD equivalents were excluded. All patients were screened for em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 19 publications
1
20
0
1
Order By: Relevance
“…Therefore, PWV measurements might be a practical tool for risk assessment, because the classic risk factors fail to operate in this particular high-risk subset of individuals 6. Indeed, a previous study found that a high PWV in subjects with a low SCORE risk (<5%), was a strong predictor of cardiovascular events,9 suggesting a better risk prediction by PWV in these individuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, PWV measurements might be a practical tool for risk assessment, because the classic risk factors fail to operate in this particular high-risk subset of individuals 6. Indeed, a previous study found that a high PWV in subjects with a low SCORE risk (<5%), was a strong predictor of cardiovascular events,9 suggesting a better risk prediction by PWV in these individuals.…”
Section: Discussionmentioning
confidence: 99%
“…This emphasises the need to refine risk further among siblings in these families. Traditional risk score algorithms poorly predict cardiovascular risk in general, but even more in relatives of patients with premature CAD 6. The latter reflects the fact that these individuals are referred for cardiovascular risk evaluation at a relatively young age, whereas in the traditional risk score algorithms age is the most potent factor determining risk.…”
mentioning
confidence: 99%
“…This emphasizes the need to further refine the risk assessment See page 261 among siblings in these families. Traditional risk algorithms poorly predict cardiovascular risk in general, but even more so in relatives of patients with premature CAD (8). This is mainly due to the fact that the question of risk mostly arises at a time when individuals are still young, whereas age is the most important risk predictor for CVD per se.…”
mentioning
confidence: 97%
“…Further, these estimation tools have limited use in the elderly (>75 years of age) because most of these systems were derived primarily from middleaged cohorts. The limited use of these tools extends to the young who, even when presenting with many unfavorable risk factors, will have low risk scores [22][23][24][25][26]. Current risk assessment tools also only examine outcomes over a defined period of time rather than assess lifetime risk; it is the latter that may offer the potential benefit from earlier attempts at initiating aggressive risk factor reduction, and the failure to assess lifetime risk does not allow assimilation of the potential salutary effects of cardiac medications for reducing event rates [27,28].…”
Section: Limitations Of Existing Scores For the Assessment Of Cardiovmentioning
confidence: 98%